A novel ion-beam-mutation effect application in identification of gene involved in bacterial antagonism to fungal infection of ornamental crops - S. Mahadtanapuk (2018)
This work is on a novel application of ion beam effect on biological mutation. Bacillus licheniformis (B. licheni formis) is a common soil bacterium with an antagonistic effect on Curcuma alismatifolia Gagnep. and Chrysanthemum indicum Linn. In an attempt to control fungal diseases of local crops by utilizing B. licheniformis, we carried out gene analysis of the bacterium to understand the bacterial antagonistic mechanism. The bacterial cells were bombarded to induce mutations using nitrogen ion beam. After ion bombardment, DNA analysis revealed that the modified polymorphism fragment present in the wild type was missing in a bacterial mutant which lost the antifungal activity. The fragments conserved in the wild type but lost in the mutant bacteria was identified to code for the thioredoxin reductase (TrxR) gene. The gene analysis showed that the TrxR gene from B. licheniformis had the expression of the antagonism to fungi in a synchronous time evolution with the fungus inhibition when the bacteria were co-cultivated with the fungi. The collective results indicate the TrxR gene responsible for the antagonism of bacteria B. licheniformis to fungal infection. © 2014 Elsevier B.V. All rights reserved.